A Seminar in Accounting Research. - Smith, John H.; Kennelly, John W. (The Accounting Review, 1970)
The article presents information on the Seminar in Accounting Research at the University of Iowa. Universities are placing increasing, and we think appropriate, emphasis upon research by faculty members. Particularly at the graduate level, ideas are volatile and subject to continuing revision. In seminar discussions, student comments take priority over faculty comments. Similarly, student papers have scheduling priority over faculty and professional contributions, with an exception made for outside guests when conflicts arise. Participants in the Seminar are, on a regular basis, graduate students in accounting and the accounting faculty. Between faculty, even "unfair" comments are allowed, but restraint is exercised in arguing with students. Faculty participation, in the manner indicated, helps to erase the illusory distinction between teaching and research, and between faculty and graduate students at the graduate level. The Seminar in Accounting Research links the diverse interests of the faculty to a common educational goal.